Developing key performance indicators to measure the progress of regional regulatory convergence and cooperation in Asia-Pacific Economic Cooperation (APEC) - Sannie Siaw Foong Chong; John C. W. Lim; Toshiyoshi Tominaga (SpringerOpen, 2018)
Abstract Regulatory convergence and cooperation among the authorities in the field of medical products (medicines and medical devices) are essential to deliver safe and efficacious products quickly to patients. APEC established the Regulatory Harmonization Steering Committee (RHSC) to advance this cause among member economies. This paper identifies four areas of appropriate regulatory practice in which APEC economies could converge, and explores the feasible processes of how APEC economies could cooperate in order to bring about realization of a maximum level of regulatory convergence by 2020.